Pancreatic Acinar Cells Employ miRNAs as Mediators of Intercellular Communication to Participate in the Regulation of Pancreatitis-Associated Macrophage Activation - Yong Zhao; Hao Wang; Ming Lu; Xin Qiao; Bei Sun; Weihui Zhang; Dongbo Xue (Mediators of Inflammation)
Macrophage activation plays an important role in the inflammatory response in acute pancreatitis. In the present study, the activation of AR42J pancreatic acinar cells was induced by taurolithocholate treatment. The results showed that the culture medium from the activated AR42J cells significantly enhanced NFκB activation in the macrophages compared to that without taurolithocholate treatment. Additionally, the precipitates obtained from ultracentrifugation of the culture media that were rich in exosomes were markedly more potent in activating macrophages compared with the supernatant fraction lacking exosomes. The results indicated that the mediators carried by the exosomes played important roles in macrophage activation. Exosomal miRNAs were extracted and examined using microarrays. A total of 115 differentially expressed miRNAs were identified, and 30 showed upregulated expression, while 85 displayed downregulated expression. Target genes of the differentially expressed miRNAs were predicted using TargetScan, MiRanda, and PicTar software programs. The putative target genes were subjected to KEGG functional analysis. The functions of the target genes were primarily enriched in MAPK pathways. Specifically, the target genes regulated macrophage activation through the TRAF6-TAB2-TAK1-NIK/IKK-NFκB pathway. As the mediators of signal transduction, miRNAs and their predicted target mRNAs regulate every step in the MAPK pathway.